ANALISIS PENGARUH LIKUIDITAS, STRUKTUR MODAL, DAN EFESIENSI OPERASIONAL TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH DI INDONESIA (Periode Tahun 2010-2014) - Syach adi Setia; Itat tatmimah (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2018)
ABSTRACT The objectives of this research is to analyze the influence of Liquidity (FDR), Capital Structure (CAR) and Operational Efficiency (ROA) to Profitability (ROA) at the Islamic Banks in Indonesia in 2010-2014. The data used in this study was obtained from the data Publication of Annual Financial Statement Sharia Bank during 2010-2104 period. The population in this study were 11 Islamic Banks in Indonesia by using the whole sample of the total population. The analysis technique used in this research is multiple linear regression that aims to obtain a comprehensive picture of the relationship between variables. While the classical assumption used in this study include autocorrelation test, normality test, multicoloniarity and heteroscedasticity test. Keywords: FDR (Financing to Deposit Ratio), CAR (Capital Adequacy Ratio), BOPO, ROA (Return on Assets).